Heterogeneity of Inclusive Green Growth and Institutions: Spatial Evidence from BRICS Plus - Binta Zulfia; Etty Soesilowati; Inayati Nuraini Dwiputri (JEJAK, 2025)
This study analyzes the dynamics of Inclusive Green Growth (IGG) and institutions in BRICS countries through descriptive analysis and clustering. Using post-pandemic cross-sectional data, the Inclusive Green Growth Index (IGGI) and Balanced Inclusive Green Growth Index (BIGGI) are calculated based on three pillars: economy, social equity, and environment. The results show that although economic and social performance is quite good, environmental performance is relatively weaker in BRICS countries. BIGGI reveals that economic growth in some countries often exceeds environmental sustainability. In the cluster analysis using hierarchical clustering through Ward's method, three distinct groups of countries were identified.  The first cluster (China, Russia, Brazil, Iran) represents large emerging economies that depend on natural resources with governance and environmental challenges. Group 2 (Ethiopia, Egypt, South Africa, India) consists of developing countries experiencing rapid growth but constrained by social, environmental, and institutional weaknesses. Group 3 (United Arab Emirates) has effective governance and strong social indicators but faces severe environmental pressures and limited democratic performance. This finding highlights the heterogeneity of BRICS Plus in terms of IGG and institutionalism. Environmental and development cooperation within BRICS Plus must adopt strategies tailored to the challenges of each group to ensure progress toward inclusive and sustainable development.